The relationship between breastfeeding contact with breastfeeding self-efficacy in Wangaya Hospital Denpasar City - Sang Ayu Kompiang Suartiningsih; Ni Komang Erny Astiti; Listina Ade Widya Ningtyas; Ni Gusti Kompiang Sriasih; I Nyoman Wirata (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2022)
Background :Breastfeeding is the best care for babies in early life. Lack of self- confidence of mothers is one of the causes of breastfeeding failure. Breastfeeding self-efficacy can be used to see or identify mothers who are at hight risk for stopping the breastfeeding process prematurely. Interventions that can improve breastfeeding self-efficacy care providing support and counseling during antenatal, perinatal and postnatal management. To achieve successful breastfeeding, WHO has set a special time for contact with lactation counselor orlactation clinic known as Breastfeeding contact.Objectives :This study aims to analyze the relationship between breastfeeding contact and breastfeeding self- efficacy in Wangaya Hospital, Denpasar City.Methods :The study was designed with an observational analytic approach with a crosssectional approach, in Februari-April 2022. The data were collected from breastfeeding mothers who bring their babies control for the first time and or 7 days old. The sampel was obtained by total sampling method, data analysis using bivariate and statistical testing using Chi-square test.Results :The results showed that of 38 respondents, were 73.68% had good breastfeeding contact and 57.89% had a good of breastfeesing self-efficacy.The results of cross tabulation, respondents who had good breastfeeding contacts and had a good breastfeesing self-efficacy were 55.26%. The results of this study indicate that there is a significant relationship between breastfeeding contact and breastfeeding self- efficacy in Wangaya Hospital Denpasar City with ρ-value is 0.001.Conclusions : Having regular breastfeeding contact can increase the breastfeeding self-efficacy.